MODERN METHODS FOR STANDARDIZING PRODUCTION PROCESSES IN MANUFACTURING - Kasimova , Gulnoza Ravshanbekovna (Educational Research in Universal Sciences, 2024)
Standardization is a critical component of efficient and effective production processes in manufacturing. This article reviews the latest research on modern methods for standardizing production processes, including the use of lean manufacturing principles, visual controls, and employee training. The findings highlight the key steps and tools for implementing standardized work, as well as the benefits of standardization for reducing waste, improving quality, and enhancing employee competency. The article also discusses common challenges and best practices for sustaining a culture of continuous improvement through process standardization.